Gravity Anomaly And Topography Induced By Repeated Fault Motions - Syed Ilias, Syed Hashim; Wan Mohd Akib, Wan Abdul Aziz (Fakulti Kejuruteraan & Sains Geoinformasi, Universiti Teknologi Malaysia., 1997)
The Accumulation Hypothesis deals with the origin of the gravity anomaly and topography around an active fault. This hypothesis was postulated that the gravity anomaly around active faults is the product of repeated fault motions; higher gravity anomaly will occured in compressed areas while lower anomaly in dilated areas. If it is the case, the topography around an active fault can also be interpreted in terms of repeated coseismic elevation change. This paper therefore presents the characters of gravity changes and topography caused by strike-slip faulting at fujimi Valley, Nagano Prefecture, Japan. In order to compute theoretical gravity changes and elevation (h), we use analytical expressions of and 8h caused by faulting on a finite rectangular plane buried in a homogeneoous half-space. The expected gravity anomaly and topography for this test area are compared with the observed data. The analyses have shown that the simple fault model yields gravity anomaly which agrees well with the observations. Similarly, the same model also generates the elevation changes that is consistent with the actual topography of the test area.